When Clients Don't Come Back: How Novice Psychotherapists Experience Premature Termination of Therapy - Saxon, Lianne (Université d'Ottawa / University of Ottawa, 2024)
Research shows that premature termination of therapy is a common and problematic occurrence in the mental health field, with at least 20% of clients leave therapy prematurely (Swift & Greenberg, 2012), before achieving their treatment goals (Swift et al., 2012). While clients continue to need mental services (Swift et al., 2012; Westmacott et al., 2010), therapists can experience burnout and a sense of failure (Klein et al., 2003; Pekarik, 1985a). A study by Piselli et al. (2011) explored the experiences of seasoned psychologists after clients terminated therapy prematurely, but to date, no in-depth qualitative study has been conducted to learn about how novice therapists experience premature termination of therapy. Client dropout rates and feelings of incompetence are more prevalent among novice therapists than their seasoned counterparts (Swift & Greenberg, 2012; Thériault & Gazzola, 2010). This thesis focuses on novice psychotherapists’ feelings, cognitions and behaviours after clients dropped out without any explanation, which is similar to ghosting in dating relationships (Pancani et al., 2022). Qualitative data was gathered from interviews with seven novice psychotherapists in Ontario, Canada. Structured Thematic Analysis Braun & Clarke, 2006; Clarke & Braun, 2017) was used, and the following main themes were identified: Therapist responses to being ghosted, how therapists processed being ghosted, nature of therapy termination, aspects of therapy delivery, elements of novice therapist development. The results highlight how novice therapists benefit from supervision and the normalization of premature termination of therapy.
Keywords: Qualitative Study; Premature Termination of Therapy; Novice Psychotherapists